2009
DOI: 10.1007/s10811-009-9435-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of the galactose-1-phosphate uridylyltransferase (galt) gene of Gracilariopsis lemaneiformis (Rhodophyta) and correlation between gene expression and agar synthesis

Abstract: We report cloning and characterization of the galactose-1-phosphate uridylyltransferase (galt) gene from the multi-cellular agar-producing marine red alga Gracilariopsis (Gp.) lemaneiformis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Meanwhile, G. edulis , which has a lower agar content, was found to have a lower gene expression level for GALT . Our results support the findings of Li et al. (2010), which suggested that high abundance of GALT transcripts may contribute to higher agar content of Gp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, G. edulis , which has a lower agar content, was found to have a lower gene expression level for GALT . Our results support the findings of Li et al. (2010), which suggested that high abundance of GALT transcripts may contribute to higher agar content of Gp.…”
Section: Discussionsupporting
confidence: 91%
“…Gross and Schnarrenberger (1995) have previously purified and characterized a GALT from a red alga, Galdieria sulphuraria . In addition, the genes encoding GALT have been cloned and characterized from Gracilaria gracilis (Lluisma and Ragan 1998) and Gracilariopsis lemaneiformis (Li et al. 2010).…”
mentioning
confidence: 99%
“…Prior to this hypothetical pathway, GALT and GME were individually verified to have a regulatory role on the content of agar. The cloning and structure analysis of GALT has been reported in Gracilaria gracilis ( Lluisma and Ragan, 1998 ) and Gracilariopsis lemaneiformis ( Li et al, 2010 ). The GALT and GME transcripts and enzyme activities were found to be highest in G. changii and lowest in G. salicornia , corresponding to their respective agar yields ( Siow et al, 2012 , 2013 ).…”
Section: Agarmentioning
confidence: 99%
“…6 ), suggesting their putative roles in regulating the biosynthesis of agar precursors. The gene expression level of these two genes had been shown to correlate with the agar content in Gracilaria and Gracilariopsis samples 24 48 49 .…”
Section: Resultsmentioning
confidence: 99%